Diskursus Tentang Ulama Perempuan di Sumatera Barat: Transformasi Gagasan Kesetaraan Syafii Maarif - Ka’bati (MAARIF, 2023)
The discourse about female Ulama is part of a social movement that is currently developing in Indonesia. The authority of the ulama, which for centuries has been dominated by men, experienced turbulence with the presence of this idea, especially after the holding of the KUPI (Congress of Indonesian Women Ulama) and the training of Female Ulama Cadres on various social media platforms. The agenda of the women’s ulama movement is also in line with Ahmad Syarii Maarif’s ideas about egalitarian attitudes in religion and the importance of awareness of gender equality to encourage social change. The research for the article is intended to see how Buya’s progressive ideas can be transformed into the religious dynamics of society in West Sumatra. Reading of this phenomenon is carried out using critical discourse analysis methods. Attention is focused on the discourse of female ulama as part of the transformation process of the idea of equality championed by Syafii Maarif. It was found that support from the government and various elements of society for the existence of female ulama still needs to be fought for because awareness of the importance of clerical authority for women has not been developed.